The Model of Supervisor Support, Work-Life Balance, Job Satisfaction, and Organizational Commitment on IT Employee Performance Moderated by Demographic Factors - Jessica Angela; Rojuaniah Rojuaniah (Jurnal Manajemen Indonesia, 2022)
This study aims to explore the effect of Supervisor Support (SS), Work-Life Balance (WLB), Job Satisfaction, and Organizational Commitment on Employee Performance moderated by age, gender, education, and marital status on IT employees. Refer to the theory and empirical evidence from previous research, we collect the data by distributing online questionnaires from November to December 2020 at some IT sector companies in the cities of Tangerang and Jakarta. The respondents are IT employees who were selected by purposive sampling method with the category non-managerial level. This study uses the PLS-SEM method. The results prove that SS, WLB, job satisfaction, and organizational commitment all have positive effects on IT employee performance. While the moderation results in this study as a whole there are no significant differences between groups of age, gender, education, and marital status with the effect of job satisfaction and organizational commitment on IT employee performance. The important managerial implications for the companies to improve the performance of IT employees are by changing the company's internal culture to be more open, creating or strengthening the warm and ‘kinship’ work environment, and organize a routine togetherness program. This will encourage positive changes for employees and be a benefit for the company. Keywords—Supervisor Support; Work-Life Balance; Job Satisfaction; Organizational Commitment; Employee Performance; Demographic Factors